2016
DOI: 10.18632/oncotarget.9244
|View full text |Cite
|
Sign up to set email alerts
|

MAPK activation andHRASmutation identified in pituitary spindle cell oncocytoma

Abstract: Pituitary spindle cell oncocytoma (SCO) is an uncommon primary pituitary neoplasm that presents with mass effect on adjacent neurovascular structures, similar to non-hormone-producing pituitary adenomas. To determine the molecular etiology of SCO, we performed exome sequencing on four SCO cases, with matched normal controls, to assess somatic mutations and copy number alterations. Our analysis revealed a low mutation rate and a copy-neutral profile, consistent with the low-grade nature of this tumor. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 55 publications
1
29
0
Order By: Relevance
“…Unfortunately, we failed to detect any nuclear somatic mutations, which have been reported in renal oncocytoma, pituitary spindle cell oncocytoma, and other pituitary adenomas [14,23,24], in our oncocytoma samples. However, frequent mtDNA mutations (averaging 30 mutations per patient) were identified (supplementary material, Table S4).…”
Section: Frequent Mtdna Mutations Lead To Mitochondrial Dysfunctionmentioning
confidence: 55%
“…Unfortunately, we failed to detect any nuclear somatic mutations, which have been reported in renal oncocytoma, pituitary spindle cell oncocytoma, and other pituitary adenomas [14,23,24], in our oncocytoma samples. However, frequent mtDNA mutations (averaging 30 mutations per patient) were identified (supplementary material, Table S4).…”
Section: Frequent Mtdna Mutations Lead To Mitochondrial Dysfunctionmentioning
confidence: 55%
“…However, this is still controversial. Recently, Miller et al [ 9 ] found a low mutation-rate and copy neutral profiles of ASCO, consistent with this tumor's low-grade nature. From 1 patient, they revealed a MEN1 frameshift-mutation (p.L117fs) and a cooccurring somatic H-RAS (p.Q61R) activating point-mutation present in primary and recurrent tumors.…”
Section: Discussionmentioning
confidence: 55%
“…SCO is a rare entity, described first in 2002 with few subsequent case reports to date . As described first by Roncaroli et al , SCO occurs most commonly in middle and older age groups with mean age of 61.6 years .…”
Section: Discussionmentioning
confidence: 84%
“…34 Miller et al have shown MAPK activity in a series of four cases of SCO. 27 Alexandrescu demonstrated expression of p-Akt, p-mTOR, and Gli2 in a single case of SCO. 35 The MAPK pathway, Akt/m-TOR pathway and Gli2 can be future potential therapeutic targets.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation